Paleopathological and traumatic changes on the mandible of the skeleton found at the Bijela - St. Margaret site (Bulletin of the International Association for Paleodontology, 2021)
The Anthropological Center of the Croatian Academy of Sciences and Arts received human bone remains  from the site of Bijela - St. Margaret derived from research conducted in 2019. The human remains found in grave number 22 caught the attention due to the atypical position of the human skeleton in the burial and trauma visible on the anterior region of the mandibular bone, along with pathological changes that are visible microscopically  and on the X-Ray scan in the same region. In this case report the description of the changes on the mandibular bone and the possible etiology is presented.Key words: burial; incision; mandible;  paleopathology;  trauma